A conceptual framework to assess the unmet travel needs in later life. (June 2018) - Luiu, Carlo; Tight, Miles; Burrow, Michael
Abstract: This study proposes a conceptual framework for improving the evaluation of unmet travel needs amongst the older population. Unmet travel needs can be defined as mobility needs that remain unfulfilled due to the inability of accomplishing needed or wished trips and activities. Gerontological and transport research are putting increasing focus on the role that mobility plays in later life. Analyses of studies investigating the relationship between ageing and mobility reveal that these are generally characterised by relying only on realised journeys and activities. However, very little has been investigated so far in terms of unrealised mobility and often where it has been investigated, with different approaches and results. This article, by means of a methodological assessment of approaches used in the literature, develops a conceptual framework that can be used to investigate which mobility needs remain unfulfilled in later life. Firstly, the concept of mobility needs in later life is addressed. This concept is then used to evaluate the most appropriate method(s) to investigate factors which influence unmet travel needs. Five main domains are identified as necessary to be considered with regard to mobility during later life: transportation; health and wellbeing; built environment; type and importance of activities and demographic background characteristics. The study concludes that an inclusive approach which considers all of the domains is needed to better define the full dimension of mobility needs among the older population. Highlights: Analyses of realised journeys do not fully describe the mobility dimension of older people. The study proposes a framework to investigate unmet travel needs in later life. The framework is based on a methodological assessment of approaches used in the literature. The framework is a construct of five interrelated domains that shape and influence mobility in later life.